Spiritual Eco-Leadership: How Religious Communities Can Model Transformative Practices to Address Climate Resilience - Mahfud Heru Fatoni; Muhammad Alfan Bahij; George Rudi Hartono Pasaribu (International Forum of Researchers and Lecturers, 2025)
This study explores the role of spiritual eco-leadership within religious communities and its potential for fostering climate resilience and sustainability. Religious communities, guided by spiritual values such as stewardship, social justice, and care for creation, have a unique position to contribute significantly to addressing climate change. Through qualitative case studies of religious communities engaged in climate-resilient practices, this research identifies key personal qualities of effective eco-leaders, examines the theological foundations driving eco-leadership, and investigates how community structures can support sustainable practices. The findings highlight the importance of qualities such as compassion, integrity, and vision in eco-leaders, which enable them to inspire collective action towards environmental sustainability. Additionally, the study uncovers the centrality of theological principles, particularly those rooted in stewardship and social justice, in guiding eco-leadership within faith-based contexts. The research also discusses the challenges these communities face, including institutional conservatism, resource constraints, and the marginalization of eco-leaders. Strategies for overcoming these barriers are proposed, emphasizing the need for education, advocacy, and interfaith collaboration. The study concludes that spiritual eco-leadership, when supported by strong theological foundations and community structures, can serve as a powerful force in driving climate resilience and promoting sustainability, both locally and globally. By fostering eco-leadership, religious communities can play a transformative role in addressing climate change and enhancing community adaptation to environmental challenges.